Determinant Factors of Help-Seeking Behavior among Students Who Engage in Self-Harm - Afifah, Prima; Hertinjung, Wisnu Sri (Universitas Muhammadiyah Surakarta, 2025)
Late adolescents or young adults are at a stage of development that is emotionally turbulent and prone to stress, so the rate of self-harm behavior in this group is still relatively high. Self-harm is the act of injuring oneself with or without suicidal intent, which, if not accompanied by seeking help, risks increasing suicidal behavior. This study aims to deeply understand the determining factors in seeking help among self-harmers. The study uses a qualitative narrative approach with five active students from Muhammadiyah University of Surakarta aged 18-25 who have engaged in self-harm at least once in the past year. Data collection techniques include interviews, observations, and documentation. Data were analyzed using the Miles & Huberman method, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the factors driving the search for help include positive experiences with seeking help, self-awareness, strong motivation to seek help, a positive attitude toward intervention, social support, ease of access to professional help, and the suitability of the help provided to the individual's needs. The barriers to seeking help were found to be the opposite of the motivating factors, plus a closed attitude and social stigma toward professional help. The sources of help came from informal and formal sources. The types of help received were instrumental support, emotional support, informational support, affiliative support, and treatment. Additionally, triggering events for self-harm and various forms of self-harm were identified. These findings contribute to the literature on the determinants of help-seeking among college students who engage in self-harm and serve as a basis for developing psychoeducation to enhance motivational factors and reduce barriers to help-seeking, particularly in the context of seeking professional help to reduce self-harm.